The importance of leasing for SME finance - Helmut Kraemer-Eis; Frank Lang (European Investment Fund (EIF), 2012)
It is well known that Micro and Small and Medium sized Enterprises (SMEs) are the backbone of the economy. Most of these companies use external financing sources like debt and equity capital to finance their activities. However, in general, in the area of SMEs' access to finance, there are market imperfections - not only in times of crisis, but on an on-going basis as a fundamental structural issue, based on uncertainty and asymmetric information between the demand side (entrepreneur) and the supply side (financial intermediary). SMEs' access to finance is often a topic of economic or financial literature. In this context, the access to debt capital and even more often the access to Venture Capital is analysed. Research on the use and role of alternative forms of finance is however rather scarce. Various surveys on access to finance show that bank loans and overdrafts are the most widespread debt financing methods for SMEs, but that alternative sources like leasing and factoring have also a high relevance. This paper puts a spotlight on the importance of leasing as integral part of the tool-set for SME finance, also against the background of market weaknesses for SME lending. It explains the mechanics and logic of SME leasing and provides latest available market information. Furthermore, the paper explains in the form of three case studies how SME leasing can be supported via credit enhancement techniques. These examples, taken from recent EIF business cases, cover very different markets and products: a securitisation transaction in Germany, a loan guarantee in France, and a structured portfolio guarantee in Lithuania.1
Keywords: G01; G10; G14; G20; G21; G23; G24; 330; Leasing; Lending; Small and Medium sized Enterprise